Study of Motivation, Training and Development on Employee Job Performance In The Directorate General of Budget of The Ministry of Finance - Werdiningsih, Werdiningsih; Rivai Zainal, Veithzal; Christina Nawangsari, Lenny (Green Publisher, 2023)
The news of the State Civil Apparatus is the main spotlight to do the job as well as possible and is expected to be an example in general and the position of the State Civil Apparatus has an important role to determine national development, physical or non-physical, to realize its success it must be obtained employees who have high responsibility, consistent, professional and visionary. To equip employees to achieve the above, it is necessary to have development and training held by the ministry so that employees have high motivation to work. Motivation is a person's drive to optimize work performance. Training and development is defined as an activity to optimize current or future work performance. Work performance is the result of a person's work to achieve quality, timeliness and ability. The purpose of this study is to determine the effect of motivation, training and development on employee work performance at the Directorate General of Budgeting, Ministry of Finance. The population of this study is employees of the Directorate General of Budgeting of the Ministry of Finance, totaling 121 people. The total sample respondents of this study were 93 employees. Questionnaires and interviews are data collection techniques in this study. Data processing and analysis used descriptive methods and multiple linear regression analysis. The results of the study state that partially the variables of motivation, training and development have a positive and significant effect on employee work performance at the Directorate General of Budgeting of the Ministry of Finance and the results shown in multiple linear regression state that the variables of motivation, training and development have a positive effect on employee work performance at the Directorate General of Budgeting of the Ministry of Finance.